Birth order and academic achievement of children in Transkei - Cherian, V I (Psychological reports, 1990)
This study investigated the relationship between birth order and academic achievement of 1021 randomly chosen Standard 7 pupils in Transkei, South Africa. The subjects ranged in age from 13 to 17 yr., with a mean of 15.6 yr. Two questionnaires, one for the pupils and the other for their parents, were administered to collect information on the birth order of children. Analysis of variance indicated a significant negative relationship between birth order of children and their academic achievement.